Characterization of the photomultiplier tubes for the scintillation detectors of GRANDProto35 experiment. (27th April 2021) - Wang, X.; Qian, X.-L.; Yu, Y.-H.; Feng, C.-F.; Martineau-Huynh, O.; Zhang, Y.; Gou, Q.-B.; Liu, W.; Feng, Y.-L.
Abstract: GRANDProto35 is the first stage of the GRAND project. It will be composed of an array of 35 radio antennas and 24 scintillation detectors in which the radio and scintillating subarrays will be triggered independently. The scintillation detector array allows to cross-check the radio array, thus quantitatively determine its detection efficiency. The photomultiplier of Hamamatsu R7725 is a candidate for the scintillation detector. The characteristics of the PMT will directly affect the resolution of the time and energy measurements and the dynamic detection range of a scintillation detector. A voltage divider circuit featured with dual-readout was designed for the PMT to cover a larger linear dynamic range (LDR). Some characteristics of the PMT were calibrated and investigated: the absolute gain, single photoelectron (SPE) energy resolution, transit time spread (TTS), linear dynamic range, and temperature dependence of the PMT gain. In this paper, details about the system setup, measurement methods, and results will be described.